Seed coating with biological agents to improve the quality of rice seeds contaminated with blast pathogens and increase seedling growth - TANTRI PALUPI (MBI & UNS Solo, 2020)
Abstract. Palupi T, Riyanto F. 2020. Seed coating with biological agents to improve the quality of rice seeds contaminated with blast pathogens and increase seedling growth. Biodiversitas 21: 683-688. The aim of this research were (1) to evaluate the compatibility of five biological agents (SP21, SP31, RP21, TP12, and TP11), (2) to evaluate the physical and physiological quality of rice seeds contaminated with Pyricularia grisea after being treated with seed coating enriched with biological agents, (3) to evaluate the effectiveness of seed coating on the incidence of blast disease and seedling growth. The first experiment tested the compatibility of five bacterial antagonists on the PSA plates. There were eight treatments in the second experiment namely seed coating enriched with SP21+SP31; SP21+RP21; SP21+TP12; SP31+RP21; RP21+TP11; fungicides; positive control (rice seeds contaminated with blast), and negative control (healthy seeds), and seven treatments in the third experiment which were the same as in experiment 2 without negative control. Parameters observed in the second experiment were: seed germination, vigor index, and growth rate, while parameters observed in the 3rd experiment were the incidence rate of blast disease and plant height. The results of experiment 1 showed that isolates SP21+SP3, SP21+RP21, SP21+TP12, SP31+RP21, and RP21+TP11 had good growth compatibility without antagonism, and they can be used as biocontrol agents. Results of experiment 2 showed that seed coating enriched with SP21+SP31 isolates has the potential to improve the physical and physiological quality of the seeds. Results of experiment 3 showed that seed coating enriched with RP21+TP11 had no incidence of blast disease up to 4 weeks after planting.